Interfacial interactions in bicomponent polymer fibers. (25th April 2018) - Leal, A. Andrés; Neururer, Olivia A.; Bian, Alex; Gooneie, Ali; Rupper, Patrick; Masania, Kunal; Dransfeld, Clemens; Hufenus, Rudolf
Abstract: The core – sheath interfacial interactions in a bicomponent thermoplastic filament have been analyzed by means of an adapted micro-mechanical approach for interfacial pull-out. The method relies on a specimen preparation procedure that selectively removes a segment of the sheath component while leaving the core intact. This adaptation of the classical pull-out method enables the controlled extraction of the exposed core from the embedded bicomponent segment. Using linear low density polyethylene (LLDPE) – polyamide 6 (PA6) filaments with a diameter of approximately 100 μm, it has been shown that the addition of 2–5 weight % maleic anhydride grafted polyethylene (MAPE) significantly increases the surface energy of LLDPE, which results in substantial improvements in the mean interfacial shear strength and work to debond. Use of 10 % wt. MAPE leads to the formation of voids which are detrimental to the mechanical properties of the core – sheath interface, despite a further enhancement of surface energy. Graphical abstract: Image 1 Highlights: Micromechanical technique is developed to probe the fiber core-sheath interface. Interfacial shear strength and work to debond for LLDPE-PA6 system are quantified. Addition of 2–5 wt% maleic anhydride-grafted PE enhances the measured properties. 10 wt% maleic anhydride-grafted PE generates voids at the LLDPE-PA6 interface. 10 wt% maleic anhydride-grafted PE yields the highest surface energy value.